Histamine inhibits the melanin-concentrating hormone system: implications for sleep and arousal - Parks, Gregory S (J Physiol, 2014)
Melanin-concentrating hormone (MCH)-producing neurons are known to regulate a wide variety of physiological functions such as feeding, metabolism, anxiety and depression, and reward. Recent studies have revealed that MCH neurons receive projections from several wake-promoting brain regions and are integral to the regulation of rapid eye movement (REM) sleep. Here, we provide evidence in both rats and mice that MCH neurons express histamine-3 receptors (H3R), but not histamine-1 (H1R) or histamine-2 (H2R) receptors. Electrophysiological recordings in brain slices from a novel line of transgenic mice that specifically express the reporter ZsGreen in MCH neurons show that histamine strongly inhibits MCH neurons, an effect which is TTX insensitive, and blocked by the intracellular presence of GDP-β-S. A specific H3R agonist, α-methylhistamine, mimicks the inhibitory effects of histamine, and a specific neutral H3R antagonist, VUF 5681, blocks this effect. Tertiapin Q (TPQ), a G protein-dependent inwardly rectifying potassium (GIRK) channel inhibitor, abolishes histaminergic inhibition of MCH neurons. These results indicate that histamine directly inhibits MCH neurons through H3R by activating GIRK channels and suggest that that inhibition of the MCH system by wake-active histaminergic neurons may be responsible for silencing MCH neurons during wakefulness and thus may be directly involved in the regulation of sleep and arousal.